Uji Kinerja Pemotong Bibit Singkong - Adnan Bahrul Ulum; Sandi Asmara; Warji Warji; Siti Suharyatun (Jurnal Agricultural Biosystem Engineering, 2023)
Preparation of cassava seeds is usually done manually so it takes a relatively long time. TEP-1 type cassava stem cutter (Petokong) is a solution to meet the needs of cassava seeds in large quantities and quickly. This study aims to determine the performance of TEP-1 type Petokong and to compare it with manual cutting using a machete and saw, as well as to find out the cuttings of the seeds produced. The research was conducted in May 2019, at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The research was conducted by cutting cassava seeds using 3 different cutting tools, namely machetes, saws and TEP-1 type petokong. The research parameters consisted of cutting capacity, seedling size uniformity, seedling damage and growth test. The results showed that the highest cutting capacity of cassava stems was TEP-1 type petokong which produced 9720 seeds/hour while cutting using a saw produced 3600 seeds/hour and the lowest was cutting using a machete, as many as 1800 seeds/hour. The uniformity of cassava seeds cut using a TEP-1 type petokong is 99%, while cutting using a saw is 95%, and using a machete is 40%. The lowest percentage of damage to seedlings resulting from cutting was using TEP-1 type petokong which was 2%, damage to seedlings using saw was 10%, and using machetes was 20%. The results of testing the growth of seedlings up to the roots explained that cutting using a TEP-1 type of petokong had perfect and spreading root growth, cutting with a saw showed uneven root growth and cutting using a machete the root growth only occurred on several sides of the cassava seedlings. Keywords: Capacity, Cassava Stems, Cutting Tools.